Methane as a Selectivity Booster in the Arc‐Discharge Synthesis of Endohedral Fullerenes: Selective Synthesis of the Single‐Molecule Magnet Dy2TiC@C80 and Its Congener Dy2TiC2@C80. Issue 45 (9th September 2015) - Junghans, Katrin; Schlesier, Christin; Kostanyan, Aram; Samoylova, Nataliya A.; Deng, Qingming; Rosenkranz, Marco; Schiemenz, Sandra; Westerström, Rasmus; Greber, Thomas; Büchner, Bernd; Popov, Alexey A.
Abstract: The use of methane as a reactive gas dramatically increases the selectivity of the arc‐discharge synthesis of M‐Ti‐carbide clusterfullerenes (M=Y, Nd, Gd, Dy, Er, Lu). Optimization of the process parameters allows the synthesis of Dy2 TiC@C80 ‐I and its facile isolation in a single chromatographic step. A new type of cluster with an endohedral acetylide unit, M2 TiC2 @C80, is discovered along with the second isomer of M2 TiC@C80 . Dy2 TiC@C80 ‐(I, II) and Dy2 TiC2 @C80 ‐I are shown to be single‐molecule magnets (SMM), but the presence of the second carbon atom in the cluster Dy2 TiC2 @C80 leads to substantially poorer SMM properties. Abstract : Carbide inclusion : The use of methane as a reactive gas dramatically increases the selectivity of the arc‐discharge synthesis of M2 TiC@C80 carbide clusterfullerenes (M=lanthanide). The new single‐molecule magnet Dy2 TiC@C80 could be readily isolated.